Necromys lasiurus: Lessons From a 38-Year Study in an Amazonian Savanna - da Rosa, Clarissa Alves; Ganança, Pedro Henrique Salomão; Lima, Albertina Pimentel; Magnusson, William Ernest (Frontiers in Ecology and Evolution, 2021)
Amazonian savannas are isolated patches of open habitats within an array of extensive tropical forest. The mammal fauna of the savannas in the Alter do Chão region (Santarém Municipality), is dominated by Necromys lasiurus, which populations has been studied by researchers of the National Institute of Amazonian Research since 1983. Here, we summarize the studies and advances made so far to better understand aspects related to population dynamics and ecology of savanna rodents and the strategies they use to persist in an environment with frequent fires subject to global climatic influences. In the Amazonian savannas the species acts as a seed disperser and population fluctuations are related to invertebrate availability, but not with fire or vegetation structure. Global climate appears to affect N. lasiurus population dynamics at local scale (i.e. plot scale) but not at the scale of all the Alter do Chão savannas. The long-term studies in Alter do Chão generated many advances about Necromys lasiurus population dynamics and ecology, including aspects relating to feeding, home range, animal-plant interactions, the effects of fire and climate change.